2015
DOI: 10.1155/2015/281528
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Inflammatory Myofibroblastic Tumor in the Left Eye with Phthisis Right Eye: A Rare Occurrence in a Child

Abstract: Inflammatory myofibroblastic tumor (IMT) is a benign pseudoneoplastic inflammatory condition with the potential for persistent local growth and recurrence that rarely affects the orbit. We report a very rare case of anterior orbital IMT in a child who presented with gradually progressive mass in left eye for 16 months. Ocular examination showed a cauliflower like exophytic mass at 360 degrees of the perilimbal area covering the entire cornea and obscuring the visualization of anterior and posterior segments. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…There is also a tenuous relationship with vasculitis, inferior vena caval thrombosis, and infections with mycobacterium avium-intracellulare complex, Epstein-Barr Virus, actinomycetes, and mycoplasma. 5,11 MRI studies of our patient showed low signal intensity on T1-weighted images and high signal intensity on T2-weighted images, reported only in 36% to 60% of cases. 13 This expression was not seen in our patient.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…There is also a tenuous relationship with vasculitis, inferior vena caval thrombosis, and infections with mycobacterium avium-intracellulare complex, Epstein-Barr Virus, actinomycetes, and mycoplasma. 5,11 MRI studies of our patient showed low signal intensity on T1-weighted images and high signal intensity on T2-weighted images, reported only in 36% to 60% of cases. 13 This expression was not seen in our patient.…”
Section: Discussionmentioning
confidence: 46%
“…The overall prognosis, however, is favorable. 9,11,15 Orbital involvement with IMT, especially bilateral, as seen in our patient, is extremely rare. It may present as extraocular muscle enlargement, as well as intraconal or extraconal masses.…”
Section: Discussionmentioning
confidence: 56%
“…There is a paucity of literature on ocular morbidities in fellow eyes of patients with phthisis bulbi with which to make comparisons, especially as some data are based on pathological studies of surgical eye specimens. 6 8 However, Kashyap et al, 10 reported findings of retinoblastoma in fellow eyes of 15 (83.3%) of their patients and Shah et al, 19 reported a case of myofibroblastic tumour in the fellow eye of a patient with phthisis bulbi. Tan et al, 11 also reported the presence of penetrating eye injuries in eight (12.5%) fellow eyes and retinal detachment in three (4.7%) fellow eyes of patients with phthisis bulbi due to sympathetic ophthalmitis.…”
Section: Discussionmentioning
confidence: 99%